ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI JENIS PROGRAM MTSN 1 LAMONGAN - Fitria Salsabilla Irzayana; Oktiana, Puja Erwinda; Emalia, Elena Sandra; Suparto, Suparto; Susanto, Heri (Universitas Muhammadiyah Metro, 2024)
In learning mathematics, there are several abilities that must be possessed in learning it, one of which is problem solving ability. The problem solving ability at MTsN 1 Lamongan is still not optimal. This was demonstrated through interviews conducted with mathematics teachers at MTsN 1 Lamongan. Therefore, the aim of this research is to describe the mathematical problem solving abilities of MTsN 1 Lamongan students in terms of the type of MTsN 1 Lamongan program. The method used by the author is a qualitative descriptive method. The data collection techniques used were through tests and interviews. The instrument used in this research is the problem solving ability instrument according to Polya. The data analysis technique is through analyzing student test results and then adjusting them to indicators of problem solving abilities. Based on the results of the research that has been carried out, the following results are obtained, in the SKS class program students are still unable to identify problems and implement strategies and are unable to formulate strategies and verify solutions. Meanwhile, in the superior program, students have been able to implement strategies but have not been able to identify problems and formulate strategies, and have not verified solutions. Lastly, regular program students have been able to formulate strategies but have not been able to identify problems and implement strategies, and have not verified solutions.